The Relationship Between Specific Pavlovian Instrumental Transfer and Instrumental Reward Probability - Cartoni, Emilio (Front Psychol, 2015)
Goal-directed behavior is influenced by environmental cues: in particular, cues associated with a reward can bias action choice toward actions directed to that same reward. This effect is studied experimentally as specific Pavlovian-instrumental transfer (specific PIT). We have investigated the hypothesis that cues associated to an outcome elicit specific PIT by rising the estimates of reward probability of actions associated to that same outcome. In other words, cues reduce the uncertainty on the efficacy of instrumental actions. We used a human PIT experimental paradigm to test the effects of two different instrumental contingencies: one group of participants had a 33% chance of being rewarded for each button press, while another had a 100% chance. The group trained with 33% reward probability showed a stronger PIT effect than the 100% group, in line with the hypothesis that Pavlovian cues linked to an outcome work by reducing the uncertainty of receiving it. The 100% group also showed a significant specific PIT effect, highlighting additional factors that could contribute to specific PIT beyond the instrumental training contingency. We hypothesize that the uncertainty about reward delivery due to testing in extinction might be one of these factors. These results add knowledge on how goal-directed behavior is influenced by the presence of environmental cues associated with a reward: such influence depends on the probability that we have to reach a reward, namely when there is less chance of getting a reward we are more influenced by cues associated with it, and vice versa.